Mario Cravo Neto and the poetry of Afro-Brazilian mythology - Castanheira, Rafael (2020)
This article deals with the work of Mario Cravo Neto in his process to break the barriers that used to separate documentary photography from the fields of the visual arts in Brazil and to question traditional pattern of this photographic gender. In this regard, his book Laróyè will be analysed in which the author, from pictures of people, animals, colours, objects and situations recorded in Salvador’s streets, Bahia, suggest the presence of the orixá Exu. The analysis of this publication showed that when the production possibilities and the use of the photographic document – especially deriving from technical, aesthetic and conceptual strategies that are closer to the ones used in artistic projects – were increased, the photographer ruptured not with the documentation per se, but with its traditional models based in the idea of photography as faithful reproduction of reality.